Isabela State University-College of Nursing’s Performance in the Nurse Licensure Examination - Rikka Klaire Villarde Galingana; Angelito Estoesta Alvarado; Kathleen Joy Costales Magtanong; Lady Claire Caalim Bautista; Ma. Maureen Nicefura Castronuevo; Reyna Agcaoili Coloma; Aira Krizelle Sotto Esteban (Health Notions, 2022)
The Nursing Licensure Examination (NLE) is a test mandatory to all aspirant for registration as professional nurses as ordered by RA 9173. The main objective was to determine and evaluate the board exam performance of the Isabela State University Echague Campus-College of Nursing Graduates from year 2015 to 2019. It is also focused on the evaluation of board exam performance of nursing graduates and from year 2015 to 2019 based from their ratings in each test categories. This study has covered 15 graduates in 2015, 10 respondents graduated in 2017, 6 graduates in 2018 and 22 for year 2019. Majority of the 53 acquired respondents are female and 19-25 years old.  Board passers of year 2019 accumulated the highest frequency among other years. Majority of nursing graduates obtained an average general rating (AVR) ranging from 78-80 percent. This study utilized Purposive Sampling in choosing desired respondents and frequency count and percentage was used in gathering data coherently which was recognized as suitable method in identifying the board examination performance. As revealed on nursing graduates ratings in each test categories, Nursing Practice 5 which contains questions with regards to Care of Clients with Physiologic and Psychological Alterations (Part C) or Care of Clients with Physiologic and Psychosocial Alterations (Part C) is the test category which nursing graduates from 2015 to 2019 find difficult. Hence, the 53 respondents have enrolled themselves in their preferred Review Centers than to self-study before taking the Nursing Licensure Examination (NLE). The result of this study is expected to help the institution improve the nursing program and identify strategies to increase board exam performance of the school and ratings of subsequent board takers. Keywords: nurse licensure examination; college of nursing; performance